Bermain dengan Kata dan Nada: Mengembangkan Kesadaran Morfologis Melalui Improvisasi Lirik Lagu di Sekolah Dasar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
Abstract. This research investigates the use of lyric improvisation to enhance morphological awareness in elementary school students at SD Negeri 1 Karang Bundar, Langsa, Aceh. Morphological awareness, defined as the understanding of the internal structure of words and the contribution of morphemes to meaning, is a vital aspect of language development. Employing a qualitative approach with a case study design, this study involved upper-grade students in structured lyric improvisation activities. The findings indicate that this method significantly improves students' abilities to recognize, manipulate, and understand morphemes within a creative and engaging context. The implications suggest that integrating arts-based pedagogical strategies, such as lyric improvisation, offers a beneficial approach to cultivate morphological awareness in young learners.